Comparative response assessment of minimally compliant low-rise conventional and base-isolated steel frames. - Erduran, Emrah (Earthquake engineering & structural dynamics.)
In this study, the multi-intensity seismic response of code-designed conventional and base-isolated steel frame buildings is evaluated using nonlinear response history analysis. The results of hazard and structural response analysis for three-story braced frame buildings are presented in this paper. Three dimensional models for both buildings are created and seismic response is assessed for three scenario earthquakes. The response history analysis results indicate that the design objectives are met and the performance of the isolated building is superior to the conventional building in the design event. For the Maximum Considered Earthquake, isolation leads to reductions in story drifts and floor accelerations relative to the conventional building. However, the extremely high displacement demands of the isolation system could not be accomodated under normal circumstances, and creative approaches should be developed to control displacements in the MCE.